Global Health: A Local Lens on Challenges and Solutions - Ratnasingam, Gobith; Kumar, Pratyush; Lionis, Christos; Ganguly, Roshni Jhan; Andoko, Dewanto; Anastasaki, Marilena (Journal of Surgical Specialties and Rural Practice, 2025)
Abstract Global health initiatives driven by western ideologies often lack adaptation to local contexts in low- and middle-income countries (LMICs), leading to persistent health inequities, inadequate infrastructure, and limited access to care, especially in rural and marginalized areas. Attainment of equitable health care in LMICs is beset by many long-standing challenges. These are a multiplicity of sociocultural, political, economic, and infrastructural determinants preventing high access to quality care, mostly among rural and marginalized communities. The far-reaching effects of such denials are rising disease burdens, unnecessary preventable mortality, and widening health inequalities. Investing in rural healthcare infrastructure by establishing primary health centers and developing a stronger rural workforce through incentives, task-shifting, and continual training will improve service delivery. This is especially important where mobile health services and telemedicine strengthen primary healthcare services in the LMICs in addressing health disparities. For sustainable solutions, there is a need to build capacity at the level, reduce external dependency, and sustain the local supply chain. One of the means to promote health literacy and trust is through community participation, participatory health initiatives, and gendersensitivity programs. The network would thus additionally strengthen the bilateral and multilateral partnerships for improving mechanisms for knowledge and policy development. To strengthen health systems and advance Sustainable Development Goal 3 with a focus on health equity, LMICs require local solutions, sustainable investments, workforce incentives, appropriate technology, capacity building, decentralized decision-making, and global partnerships.